Professional Burnout among Catholic Religious Sisters in Italy: An Empirical Enquiry Exploring the Protective Role of Quality of Community Life - Crea, Guiseppe (Research in the social scientific study of religion, 2015)
This study set out to examine three questions regarding the prevalence and correlates of burnout among a sample of 194 Catholic religious sisters in Italy who completed the Maslach Burnout Inventory alongside the Big Five Factor model of personality and the Index of Community Satisfaction. Regarding the prevalence of burnout, the data demonstrated that the mean scale scores of these sisters on emotional exhaustion, depersonalization, and personal accomplishment all came within the normal range proposed by the test manual. Regarding the personality correlates of burnout, the data demonstrated that the two key personality predictors of higher burnout scores among these sisters were high neuroticism scores and low agreeableness scores. High openness scores also predicted higher personal accomplishment, but were unrelated to differences in emotional exhaustion or in depersonalization. Regarding predictors of community life, after taking individual differences in age and personality into account, higher levels of community satisfaction were associated with lower levels of emotional exhaustion and lower levels of depersonalization, but unrelated to levels of personal accomplishment. This finding suggests that a good quality of community life among religious sisters may enhance resilience against burnout, while a poor quality of community life among religious sisters may exacerbate burnout.